Feasibility Analysis of Beef Cattle Farming in Semangga District, Merauke Regency - Sapi’i, M Agung; Untari, Untari; Rizal, Abdul (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2024)
The aim of this research is to analyze the feasibility of beef cattle farming in the Semangga District, Merauke Regency. The selection of the area was carried out purposively with the consideration that Semangga District is the highest center for beef cattle production in Merauke Regency. The sample withdrawal method uses the Slovin Formula. The sample in the study amounted to 67 samples from a population of 200. Data collection was carried out through observations, interviews and questionnaires. The data analysis method uses qualitative descriptive analysis. The results of the research show that the total production cost of beef cattle farming at the research location is IDR105.815,287-/year with an average receipt of IDR117.901,036-/year and income IDR12.085,749-/Year The results of the R/C Ratio analysis show a value of 1.11, meaning that the beef cattle business is feasible to develop.